UMKM Pemberdayaan Bogem “Somano” Dikawasan Mangrove Surabaya Dalam Upaya Peningkatan Omset Pasca Covid-19 - Yanna Eka Pratiwi; Ujang Syaiful Hidayat; Endang Muryani; Hariyanto, Dwi Widi; Supartini; Siwidyah Desi Lastianti; Novelia Asita Mranani; Naam Fajar Basroni; Indra Wijayanto; Iwan Wahyu Susanto; Ida Budiarti (Universitas Merdeka Surabaya, 2022)
This community service activity is carried out by the economics faculty of Merdeka University Surabaya which consists of lecturers and students from two study programs, namely the management study program and the accounting study program. This program focuses on transferring soft skills in the marketing mix to MSMEs empowering mangrove fruit in the mangrove ecotourism area of Surabaya. This activity was chosen specifically as a result of the initial observation that there are still many holes in Somano's MSME promotion practice. The soft skill transfer was successfully implemented and received a positive response from MSME Somano. Various marketing mix knowledge that is transmitted can be easily understood and accepted, and some in the context of improving Somano's MSME marketing strategy are well received.